Beyond the Cubital Tunnel: Use of Adjunctive Procedures in the Management of Cubital Tunnel Syndrome. (March 2023) - Evans, Adam; Padovano, William M.; Patterson, J. Megan M.; Wood, Matthew D.; Fongsri, Warangkana; Kennedy, Carie R.; Mackinnon, Susan E.
Background: Our management of cubital tunnel syndrome has expanded to involve multiple adjunctive procedures, including supercharged end-to-side anterior interosseous to ulnar nerve transfer, cross-palm nerve grafts from the median to ulnar nerve, and profundus tenodesis. We also perform intraoperative brief electrical stimulation in patients with severe disease. The aims of this study were to evaluate the impact of adjunctive procedures and electrical stimulation on patient outcomes. Methods: We performed a retrospective review of 136 patients with cubital tunnel syndrome who underwent operative management from 2013 to 2018. A total of 38 patients underwent adjunctive procedure(s), and 33 received electrical stimulation. A historical cohort of patients who underwent cubital tunnel surgery from 2009 to 2011 (n = 87) was used to evaluate the impact of adjunctive procedures. Study outcomes were postoperative improvements in Disabilities of the Arm, Shoulder, and Hand (DASH) questionnaire scores, pinch strength, and patient-reported pain and quality of life. Results: In propensity score–matched samples, patients who underwent adjunctive procedures had an 11.3-point greater improvement in DASH scores than their matched controls ( P = .0342). In addition, patients who received electrical stimulation had significantly improved DASH scores relative to baseline (11.7-point improvement, P < .0001), whereas their control group did not. However, when compared between treatment arms, there were no significant differences for any study outcome. Conclusions: Patients who underwent adjunctive procedures experienced greater improvement in postoperative DASH scores than their matched pairs. Additional studies are needed to evaluate the effects of brief electrical stimulation in compression neuropathy.